Advanced glycation end products induce glomerular sclerosis and albuminuria in normal rats. - Vlassara, H (1994)
High levels of tissue advanced glycation end products (AGEs) that result from the spontaneous modification of proteins by glucose occur in diabetes and aging. To address the potential pathogenic role of AGEs in the glomerulosclerosis of diabetes or nephrosclerosis of aging, doses of AGE-modified rat albumin (25 mg per kg per day, i.v.) sufficient to elevate circulating AGE levels to the range of diabetic serum were administered daily to healthy rats alone or in combination with the AGE inhibitor aminoguanidine. After 5 months, the AGE content of renal tissues in AGE-treated rats rose to 50% above controls (P < 0.025), whereas serum contained 2.8-fold greater AGE levels (P < 0.025). Light and electron microscopy of kidneys from AGE-treated rats revealed a more than 50% increase in glomerular volume compared to controls (P < 0.001), significant periodic acid/Schiff reagent-positive deposits, basement membrane widening, and mesangial extracellular matrix increase and indicated significant glomerulosclerosis compared to untreated (P < 0.002) or albumin-treated controls (P < 0.002). These changes were associated with significant loss of protein (P < 0.005) and albumin (P < 0.002) in the urine of AGE-treated rats compared to controls. Cotreatment with aminoguanidine markedly limited both the structural and functional defects. These in vivo data demonstrate that AGEs influence glomerular structure and function in a manner leading to glomerulosclerosis. The effects are AGE-specific, as they are ameliorated by a pharmacological AGE inhibitor, aminoguanidine.